2022
DOI: 10.1002/ajh.26686
|View full text |Cite|
|
Sign up to set email alerts
|

Ponatinib after failure of second‐generation tyrosine kinase inhibitor in resistant chronic‐phase chronic myeloid leukemia

Abstract: Ponatinib, the only third-generation pan-BCR::ABL1 inhibitor with activity against all known BCR::ABL1 mutations including T315I, has demonstrated deep and durable responses in patients with chronic-phase chronic myeloid leukemia (CP-CML) resistant to prior second-generation (2G) TKI treatment. We present efficacy and safety outcomes from the Ponatinib Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL) and CML Evaluation (PACE) and Optimizing Ponatinib Treatment in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
3
30
0
1
Order By: Relevance
“…Ponatinib is best known for its activity against most BCR::ABL1 mutations, including T315I, and is currently approved for use in patients with prior exposure to ≥2 TKIs or harbor T315I mutation; the recommended starting dose is 45 mg, to be reduced to 15 mg at MR2 20 . In the current issue of AJH , Kantarjian et al present an updated report on the use of ponatinib in two previously reported clinical trials: Ponatinib Ph1‐positive ALL and CML evaluation (PACE; starting dose 45 mg/day) and Optimizing Ponatinib Treatment in CP‐CML (OPTIC; patients randomly assigned to 45, 30 or 15 mg/day with responders reducing ponatinib dose to 15 mg/day) 21 . The study focused on CML‐CP patients participating in PACE ( n = 257; median follow‐up 57 months) and OPTIC ( n = 93; median follow‐up 32 months).…”
Section: Imatinib (Gleevec®) Dasatinib (Sprycel®) Nilotinib (Tasigna®...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ponatinib is best known for its activity against most BCR::ABL1 mutations, including T315I, and is currently approved for use in patients with prior exposure to ≥2 TKIs or harbor T315I mutation; the recommended starting dose is 45 mg, to be reduced to 15 mg at MR2 20 . In the current issue of AJH , Kantarjian et al present an updated report on the use of ponatinib in two previously reported clinical trials: Ponatinib Ph1‐positive ALL and CML evaluation (PACE; starting dose 45 mg/day) and Optimizing Ponatinib Treatment in CP‐CML (OPTIC; patients randomly assigned to 45, 30 or 15 mg/day with responders reducing ponatinib dose to 15 mg/day) 21 . The study focused on CML‐CP patients participating in PACE ( n = 257; median follow‐up 57 months) and OPTIC ( n = 93; median follow‐up 32 months).…”
Section: Imatinib (Gleevec®) Dasatinib (Sprycel®) Nilotinib (Tasigna®...mentioning
confidence: 99%
“…20 45, 30 or 15 mg/day with responders reducing ponatinib dose to 15 mg/day). 21 The study focused on CML-CP patients participating in PACE (n = 257; median follow-up 57 months) and OPTIC (n = 93; median follow-up 32 months). In PACE, 42%, 46% and 47% of patients achieved MR2 at 1, 2 and 5 years; in OPTIC, 52% and 57% achieved MR2 at 1 and 2 years, respectively.…”
mentioning
confidence: 99%
“…Taken together, 1e is a potent Bcr-Abl inhibitor that has been approved for the treatment of CML patients who are resistant or intolerant to Imatinib, Dasatinib, or Nilotinib, and studies have confirmed that 1e can be effective in a variety of other cancers [ 30 ]. In the future, the clinical safety and patient tolerability profile of 1e need to be further explored.…”
Section: Indole/azaindole/oxindole-based Approved Atp-competitive Kin...mentioning
confidence: 99%
“…In the second‐line setting (after frontline TKI failure due to either disease resistance or TKI intolerance), different TKI options are available for patients with CML‐CP and disease resistance or intolerance to frontline therapy 5–7 . Among patients who fail second‐line TKI, the outcome is less favorable, perhaps due to disease resistance and less availability of more effective TKIs in this setting 3,8–10 . The use of alternative second‐generation TKIs (2G‐TKIs) in the third‐line setting is associated with modest response rates, where less than a third of the patients achieve a complete cytogenetic response (CCyR) 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Among patients who fail second-line TKI, the outcome is less favorable, perhaps due to disease resistance and less availability of more effective TKIs in this setting. 3,[8][9][10] The use of alternative second-generation TKIs (2G-TKIs) in the third-line setting is associated with modest response rates, where less than a third of the patients achieve a complete cytogenetic response (CCyR). 11,12 Other options available as third-line therapy include the third-generation BCR::ABL1 TKIs like ponatinib, the novel third-generation TKIs like asciminib and the investigational TKI olverembatinib.…”
mentioning
confidence: 99%